Activities of international, medical and humanitarian NGOs in Ukraine under martial law - Volodymyr V. Shablystyi; Kseniia E. Kosiachenko; Vasyl S. Berezniak; Roman A. Katorkin; Viktor Y. Konopelskyi (Health for All Nations, 2023)
As a result of Russia's full-scale military offensive on the territory of Ukraine, numerous international, non-governmental organizations have commenced providing assistance to the population through the implementation of different programs. Such assistance is manifested in various aspects, from humanitarian to financial. This article outlines the experience and legal basis for the operation of several international, non-governmental, medical and humanitarian organizations in Ukraine working under martial law imposed as a result of the war. To the purpose and objectives of the study, the work uses a combination of general and special methods of scholarly knowledge. The article uses the doctrinal provisions of science on the legal framework for the activities of international, medical and humanitarian, non-governmental organizations in Ukraine, as well as statistical data on the activities of public associations during the period of martial law. This study was conducted taking into account the experience of non-governmental organizations in other countries. The authors found that during the legal regime of martial law in Ukraine, international, non-governmental organizations such as Medecins Sans Frontieres, the International Committee of the Red Cross, and Oxfam play a leading role in providing humanitarian and medical assistance to war victims. These organizations play a key role in promoting democracy while helping to mitigate violence and the psychological trauma of war victims. It is the authors' contention that such assistance furthers democratic governance, helps curb violence, and addresses the psychological trauma occasioned by the war.